Specificity of fleas associated with opossums in a landscape gradient in the Paranaense Rainforest Ecoregion - Urdapilleta, Mara; Lamattina, Daniela; Burgos, Eliana Florencia; Salomón, Oscar Daniel; Lareschi, Marcela (Zootaxa, 2023)
The degree of host specificity of fleas varies from highly specific (monoxenous) to opportunistic (polyxenous). Specific parasite-host associations can be observed among some flea families and tribes and mammalian orders, such as fleas of the tribe Tritopsyllini (Ctenophthalmidae, Doratopsyllinae) and opossums (Didelphimorphia). Specimens of the family Didelphidae are common hosts of fleas of the genus Adoratopsylla (Ewing, 1925). In northern Argentina, Adoratopsylla (Adoratopsylla) antiquorum antiquorum (Rothschild, 1904) and Adoratopsylla (Tritopsylla) intermedia intermedia (Wagner, 1901) were recorded preferentially parasitizing opossums. In order to study parasite/host relationships, fleas were collected from opossums captured in different environments in the Paranaense Rainforest ecoregion, northern Misiones province between 2016 and 2018. A total of 287 fleas were collected from 110 opossums. The fleas were identified as Pulicidae: Ctenocephalides felis felis (Bouché, 1835); Rhopalopsyllidae: Polygenis (Polygenis) rimatus (Jordan, 1932), Polygenis (Polygenis) roberti roberti (Rothschild, 1905); Ctenophthalmidae: A. (T.) i. intermedia, A. (A.) a. antiquorum, Adoratopsylla (Adoratopsylla) antiquorum ronnai (Guimarães, 1954). We report for the first time in Argentina a male specimen of A. (A.) a. ronnai collected on Didelphis albiventris (Lund, 1840) (Didelphidae), and male and female specimens of P. (P.) r. roberti collected on Didelphis aurita (Wied-Neuwied, 1826), and we describe the expansion of the geographic and host distribution of fleas to the Paranaense Rainforest ecoregion. Our records reinforce the specific association between Adoratopsylla and Polygenis fleas and didelphid opossums, mentioned in the literature for the Atlantic Forest ecoregion in Brazil. Furthermore, we observed that flea communities in opossums change in a landscape gradient, with invasive cat fleas and euryxenous fleas common in anthropized areas, and endemic fleas common in natural areas. Our results underline the importance for public health and veterinary medicine the analysis of flea circulation between wild and urban environments due to the risk of pathogen transmission.